2020
DOI: 10.3892/etm.2020.9243
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR4/MyD88/NF‑κB signaling in the contrast‑induced injury of renal tubular epithelial cells

Abstract: The aim of the present study was to explore the role of toll-like receptor 4 (TLR4)/myeloid differentiation primary response 88 (MyD88)/nuclear factor (NF)-κB signaling in the contrast-induced injury of renal tubular epithelial cells, and to investigate the potential mechanisms. HK-2 cells cultured in vitro were randomly divided into six groups as follows: i) The blank group; ii) the iohexol group; iii) the NF-κB RNAi group (NF-κB siRNA + iohexol); iv) the TLR4 RNAi group (TLR4 siRNA + iohexol); v) the NF-κB b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…13 Cellular Microbiology cytokine levels of IL-1β and IL-6, which is consistent with the report that K. marxianus has anti-inflammatory potential [44], and its treatment may be beneficial to improve gut inflammation since gut is a source of inflammation in CHD [48]. The inflammatory TLR4/NF-κB axis promotes KI development and progression [14,49], and the inhibition of the signaling pathways has been widely reported to control KI development [15,50]. The present findings also approved that K. marxianus treatment shows protective function for KI by downregulating the expression of TLR4/ NF-κB (Figure 9).…”
Section: Discussionsupporting
confidence: 86%
“…13 Cellular Microbiology cytokine levels of IL-1β and IL-6, which is consistent with the report that K. marxianus has anti-inflammatory potential [44], and its treatment may be beneficial to improve gut inflammation since gut is a source of inflammation in CHD [48]. The inflammatory TLR4/NF-κB axis promotes KI development and progression [14,49], and the inhibition of the signaling pathways has been widely reported to control KI development [15,50]. The present findings also approved that K. marxianus treatment shows protective function for KI by downregulating the expression of TLR4/ NF-κB (Figure 9).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, in MyD88−/− mice, the anti-apoptotic bcl-2 protein is elevated compared to wild type mice, which results in protection from death [82]. In vitro analyses confirmed the notion that TLR4/MyD88/NF-κB axis regulates inflammatory response and apoptosis after renal injury [89]. In the context of renal damage, TLR4 can be activated by alarmins (endogenous ligands for TLR4; i.e., HGMB1 and Hsp70) as a consequence of cellular stress, amplifying kidney injury [90].…”
Section: Tlr4 Mediated Effectsmentioning
confidence: 55%
“…By promoting inflammation, programmed cell death, and endoplasmic reticulum stress, TLR4 has been linked to several acute and chronic renal disorders ( 34 ). Studies on contrast-induced AKI have found that contrast media increased the expression of TLR4 and up-regulate TLR4-related downstream inflammatory pathways ( 35 , 36 ). Ginsenoside Rb1/atorvastatin both attenuate renal injury by inhibiting the activation of TLR4)/NF-κB signaling pathway triggered by contrast media ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%